HARMONIZATION OF THE AGRICULTURAL POLICY OF THE REPUBLIC OF SERBIA WITH THE AGRICULTURAL POLICY OF THE EUROPEAN UNION - Stojiljković, Marija; Raicevic, Jelena; Djurkovic, Marija (Economics of Agriculture, 2025)
This paper focuses on agricultural policy as a set of measures that influence the functioning, growth, and improvement of agriculture in a country like the Republic of Serbia. Serbia’s agricultural policy is intertwined with various national policy activities and depends on the common budget resources, facing constant pressures and challenges. The key objective is to analize the alignment of Serbia’s agricultural policy (SAP) measures with the agricultural policy of the European Union. The results of this research indicate that although the SAP has experienced decline and serious crises, structural and systemic changes in agricultural policy have occurred in recent years through integration, the adoption of standards and regulations, and significant financial investments. Harmonization with EU laws, accompanied by increasing financial assistance, enables further development of Serbia’s agricultural policy. However, several limiting factors still exist in Serbia concerning alignment with the EU’s agricultural policy, such as the unfavorable position of rural areas, low educational levels of the population, and depopulation of rural regions.